Study on the application of marine microalgal biomass of Schizochytrium mangrovei PQ6 used for fresh feed of snout otter clam (Lutraria rhyncheana Jonas, 1844) - Thu, Ngo Hoai; Lan Anh, Hoang Thi; Hong, Dang Diem (Academia Journal of Biology, 2012)
﻿Schizochytrium mangrovei PQ6 isolated from coastal area of Phu Quoc Island, Kien Giang province on 2006 - a heterotrophic marine microalga which possesses a large amount of essential polyunsaturated fatty acids (PUFAs) such as eicosapentaenoic acid (20: 5n-3, EPA), docosahexaenoic (22: 6n-3, DHA) acid anddocosapentaenoic acid (C22: 5n-6, DPA). These PUFAs play an important role in health human and animals, especially aquaculture. Schizochytrium is considered as a potential marine microalga for supplying PUFAs with high quality and stability compared with traditional fish oil.Nowadays, the study on application of Schizochytrium for feeding animals in aquaculture (e.g. for rotifer, krill’s, shrimp’s larvae, etc.) which was carried out not only in the world but also in Vietnam hasobtained optimistic results. In this paper, we have presented the initial results of the application of Schizochytrium frees biomass as live food for parents of Snout otter clam (Lutraria rhyncheana Jonas, 1844) - one of animals which have high nutritional value, high economic and popular culture in aquaculture farms atthe present. After 15 days of experiment, in comparison with control which fed with autotrophic marine microalgae as Isochrysis galbana, Chaetoceros gracilis, Nannochloropsis aculata..., Snout otter clams in experiment group had fresh weight, long, wide and thick of body increasing in 63.79, 10.37; 11.41 and 11.94%, respectively; total lipid and PUFA contents increased in 10 and 41.94%; PUFAs/saturated fatty acids ratio increased in 1.89 times, contents of protein, macro and micro- elements increased in 10% and survival rate of snout otter clam’s larvae increased in 20-30%. The obtained results above mentioned have opened newprospect in utilization fresh biomass of Schizochytrium for Snout otter clam as well as animals in aquaculture in generally in order to contribute improving quality of aquaculture products, decreasing in the productive cost and increasing in the competition of produce on the market.